Free radical effects on membranes - Matalon, Sadis; Patel, Rakesh P.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier/Academic Press, 2008)
Current Topics in Membranes provides a systematic, comprehensive, and rigorous approach to specific topics relevant to the study of cellular membranes. Each volume is a guest edited compendium of membrane biology. Articles covered in the volume include * Provides overviews on biomembranes and the impact their physico-chemical properties have on reactive species reactivity * Focuses is on reactive species and control of cell-signaling pathways * Illustrates the concept that different reactive species can modulate function of specific membrane ion channels in different tissues, including sodium channels, chloride channels, sodium-potassium ATPases and calcium channels in both plasma and intracellular organelle membranes.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cell membranes; Cellular control mechanisms; Biological transport; Free radicals (Chemistry) -- Pathophysiology; Cellular signal transduction; Cell Membrane; Free Radicals; Signal Transduction; SCIENCE -- Life Sciences -- Cell Biology; Biological transport; Cell membranes; Cellular control mechanisms; Cellular signal transduction; Free radicals (Chemistry) -- Pathophysiology; Electronic books